Novel mechanisms and signaling pathways of esophageal ulcer healing: the role of prostaglandin EP2 receptors, cAMP, and pCREB - Ahluwalia, Amrita (American Physiological Society, 2014)
Clinical studies indicate that prostaglandins of E class (PGEs) may promote healing of tissue injury e.g., gastroduodenal and dermal ulcers. However, the precise roles of PGEs, their E-prostanoid (EP) receptors, signaling pathways including cAMP and cAMP response element-binding protein (CREB), and their relation to VEGF and angiogenesis in the tissue injury healing process remain unknown, forming the rationale for this study. Using an esophageal ulcer model in rats, we demonstrated that esophageal mucosa expresses predominantly EP2 receptors and that esophageal ulceration triggers an increase in expression of the EP2 receptor, activation of CREB (the downstream target of the cAMP signaling), and enhanced VEGF gene expression. Treatment of rats with misoprostol, a PGE(1) analog capable of activating EP receptors, enhanced phosphorylation of CREB, stimulated VEGF expression and angiogenesis, and accelerated esophageal ulcer healing. In cultured human esophageal epithelial (HET-1A) cells, misoprostol increased intracellular cAMP levels (by 163-fold), induced phosphorylation of CREB, and stimulated VEGF expression. A cAMP analog (Sp-cAMP) mimicked, whereas an inhibitor of cAMP-dependent protein kinase A (Rp-cAMP) blocked, these effects of misoprostol. These results indicate that the EP2/cAMP/protein kinase A pathway mediates the stimulatory effect of PGEs on angiogenesis essential for tissue injury healing via the induction of CREB activity and VEGF expression.